Revitalización urbana en la comuna 10 de la ciudad de Neiva – Huila (2021)
This research project proposed an urban revitalization for the tenth district of Neiva - Huila, at the protection zone of the ceiba river according to different aspects such us economics, socials, urbans and enviromental identified in this zone, giving it an urban model plan that mitigates the impacts generated by population growth, as a goal optimizing the improvement of public spaces taking into account the environment. In the same way, it develops a methodology based on an urban regional analysis, in order to search the issues from different points of views.